Unusual Synergy: Undergraduate Research and Civic Engagement Initiatives at Community Colleges - Chaffin, LaTasha; Rivera, Marisol Violanda; Del Rio, Elizabeth; Gray, Tremeisha; Miranda, Giselle; Osei, Bernard Kwame; Henry, Raymesha; Royer, Brenda Eliza Sevilla (Experiential Learning and Teaching in Higher Education, 2025)
Centers for Undergraduate Research and Centers for Civic Engagement are rare at the Community College level. With two such Centers both launched in 2023 at a Midwestern Community College, we are endeavoring to examine how intentional mentoring efforts in undergraduate research and civically engaging students in the political process impact students' political efficacy and interest in research careers and careers in public service. We also examine how the research and civic engagement projects these community college students are participating in influence their desire to pursue graduate level education. The Director and Co-Directors of these two Centers along with the community college student civic leaders and undergraduate research scholars will offer evidence-based practices on how to implement and grow such Centers with experiential learning practices at peer institutions.